Association between smoking and glycemic control in diabetic patients: Results from the Risk Evaluation of cAncers in Chinese diabeTic Individuals: A lONgitudinal (REACTION) study: 吸烟与糖尿病患者血糖控制的相关性研究:来自中国2型糖尿病患者恶性肿瘤发生风险的纵向研究(REACTION)的发现. Issue 5 (18th January 2018) - Peng, Kui; Chen, Gang; Liu, Chao; Mu, Yiming; Ye, Zhen; Shi, Lixin; Zhao, Jiajun; Chen, Lulu; Li, Qiang; Yang, Tao; Yan, Li; Wan, Qin; et al.
Abstract: Background: A number of primary studies suggested that active smoking could be independently associated with incident diabetes. However less is known about the effect of active smoking and smoking cessation on glycemic control in patients with diabetes. The aim of this study was to evaluate the associations of active smoking and smoking cessation with glycemic control in diabetic patients. Methods: The present was a cross‐sectional study of 10 551 men and 15 297 women with diabetes from the Risk Evaluation of cAncers in Chinese diabeTic Individuals: a lONgitudinal (REACTION) study. Risk factors for glycemic control and the association of active smoking with glycemic control were evaluated using logistic regression models. Poor glycemic control was defined as HbA1c ≥7.0%. Results: Current smokers have an increased risk of poor glycemic control, and the multivariable‐adjusted odds ratio (OR) and 95% confidence intervals (CI) of HbA1c ≥7.0% with current smoking were 1.49 (1.35–1.66) in men and 1.56 (1.13–2.15) in women. Further analysis demonstrated a dose‐dependent relationship between active smoking and the risk of poor glycemic control in men. Former smokers who quit smoking for <10 years remained at increased risk of poor glycemic control, with the risk leveling off after 10 years of smoking cessation compared with non‐smokers, but risk in former smokers was significantly lower than that in current smokers. Conclusions: Active smoking is a modifiable risk factor for poor glycemic control in Chinese diabetic patients. Abstract : Highlights Active smoking was associated with an increased risk of prevalent poor glycemic control in middle‐aged or elderly diabetic adults. Men who quit smoking for <10 years remained at increased risk for prevalent poor glycemic control compared with never smokers, and the risk leveled off after 10 years of smoking cessation. Smoking cessation was associated with improvement in glycemic control compared with current smoking.